Multifractality of stride-to-stride variations in adolescent runners is sensitive to endurance training - Chalitsios, C.; Stergiou, N.; Nikodelis, T. (Sports Biomechanics, 2025)
This study investigated the impact of training on stride-to-stride variations in adolescent runners. It was hypothesised that training would significantly affect the magnitude and temporal structure of stride-to-stride variability during running. Twelve competitive adolescent runners (age: 16.3 ± 0.81) performed two 8-minute all-out running tests on a 400-m track, once at the start of the off-season (R1) and again after 6 weeks of structured training (R2). The study measured stride variability using the coefficient of variation (CV), monofractal analysis (DFA-a), and multifractal spectrum metrics (W and WAsym). No significant differences in CV and DFA-a between the two tests, suggesting stable magnitude and temporal structure of stride-to-stride variability in terms of monofractality. However, significant changes were observed in the multifractal spectrum, with a reduction in W and a shift in WAsym towards more symmetrical values after training. These results indicate that multifractal dynamics are a more sensitive metric to evaluate the effects of training on stride-to-stride variations in adolescent runners. The reduction of both W and WAsym leads to the assumption that alterations in neuromuscular control and adaptability in adolescent runners occurred due to training. Future research should further explore the utility of multifractal metrics in monitoring training progress and optimising performance in young athletes.